Analisis Beban Dan Stres Kerja Perawat Hubungannya Dengan Keseimbangan Kehidupan Kerja Perawat Perioperatif: Analisis Beban Dan Stres Kerja Perawat Hubungannya Dengan Keseimbangan Kehidupan Kerja Perawat Perioperatif - Hikmatul Zainiyah; Tri Anjaswarni; Tri Johan Agus Yuswanto; Kissa Bahari (Jurnal Keperawatan Terapan, 2025)
Workload and stress for nurses in hospitals, especially in operating rooms, are conditions that require special attention. This is important because nurses working in operating rooms face high work demands, which can cause stress. If not managed properly, this stress can have a negative impact on nurses' performance and work-life balance. Objective: This study aims to analysis the relationship between workloads and work-related stress with the quality of work-life balance among perioperative nurses at Lavalette Hospital in Malang. Methodology: This study employs a correlational design with a cross-sectional approach. The study population consists of all perioperative nurses at Lavalette Hospital in Malang, using total sampling involving 34 respondents. Data analysis used the Spearman's rank correlation test. Research results: There was a significant relationship between workload and work-life balance with a p-value of 0.001 (< 0.05) and a correlation coefficient of r = -0.535 (strong relationship). Similarly, there was a significant relationship between work stress and work-life balance with a p-value of 0.002 (< 0.05) and r = -0.514 (strong relationship). The negative correlation indicates that the higher the workload and work stress experienced, the lower the level of work-life balance among perioperative nurses. Conclusions and Recommendations: Ongoing efforts are needed from nurses to enhance their competencies, implement effective time management, and optimize work stress management. For healthcare institutions, it is recommended to regularly enhance nurses' capacity through training, provide performance- based rewards, and establish effective communication regarding career progression